An alternative approach to the Adem relations in the mod p Steenrod algebra - Turgay, Neşet Deniz (Academic Publishing House, 2017)
Let A denote the Bockstein-free part of the mod p Steenrod algebra, where p is a fixed odd prime, and let F denote the Leibniz-Hopf algebra. We study the map ?* dual to the Hopf algebra epimorphism ?: F ? Z/p ? A, which gives an alternative approach to the Adem relations in A. We also investigate Milnor’s Hopf algebra conjugation formula for A* in terms of the Ehrenborg’s conjugation formula for F* ? Z/p. © 2017, Academic Publishing House. All rights reserved.
Keywords: Adem relations; An-tipode; Hopf algebra; Leibniz-Hopf algebra; Quasisymmetric functions; Steenrod algebra